Human Primpol1: a novel guardian of stalled replication forks. (5th November 2013) - Im, Jun‐Sub; Lee, Kyung Yong; Dillon, Laura W; Dutta, Anindya
Abstract : Huang and colleagues identify a human primase‐polymerase that is required for stalled replication fork restart and the maintenance of genome integrity.